18th International Conference on Dependability and Quality Management ICDQM-2015 (Proccedings Review) - Pokorni, Slavko J. (Vojnotehnički glasnik / Military Technical Courier, 2015)
The article gives an overview of the conference overal results and its significance, presenting the international programme committee and the working areas of the 17th DQM International Conference on Dependability and Quality Management ICDQM 2014 and 5th DQM International Conference on Life Cycle Engineering and Management (papers printed in Serbian, English and Russian), which was held under the same acronym ICDQM-2014. The number and structure of papers presented at both conferences are given while the papers discussed in more detail are only those from the participants from the Armed Forces and the Ministry of Defense of the Republic of Serbia in Sections: Military Engineering, Quality Engineering, Reliability Engineering, Industrial Engineering, Systems Engineering, Energy Efficiency and Lean Production. This year’s conference has had the biggest number of papers presented by the participants from the Armed Forces and the Ministry of Defense of the Republic of Serbia so far.
Keywords: quality; reliability; military engineering; conference; review